Answer:
ur question is more clarification
Step-by-step explanation:
Answer:
4. (6,0)
Step-by-step explanation:
Plug the points into the equation.
6+3(0)=6
6+0=6
6=6
Answer:
151
Step-by-step explanation:
<h2>(1)</h2><h2> =(a+b)(3c-d)</h2><h2> =a(3c-d)+b(3c-d)</h2><h2> =3ac-ad+3bc-bd</h2>
<h2>(2)</h2><h2> =(a-b)(c+2d)</h2><h2> =a(c+2d)-b(c+2d)</h2><h2> =ac+2ad-bc-2bd</h2>
<h2>(3)</h2><h2> =(a-b)(c-2d)</h2><h2> =a(c-2d)-b(c-2d)</h2><h2> =ac-2ad-bc+2bd</h2>
<h2>(4)</h2><h2> =(2a+b)(c-3d)</h2><h2> =2a(c-3d)+b(c-3d)</h2><h2> =2ac-6ad+bc-3bd</h2>
Answer:
they ran 5 and 2 and half hour
Step-by-step explanation:
they ran 5 and 2 and half hour